1992
DOI: 10.1002/pola.1992.080300202
|View full text |Cite
|
Sign up to set email alerts
|

A solid‐state 13C‐NMR study of crosslinking in polybutadiene by γ radiation: Effect of microstructure and dose

Abstract: Solid‐state 13C NMR spectroscopy has been used to determine the decrease in CC bonds, formation of crosslinks and cis to trans isomerization during the γ irradiation of (a) > 99% cis, 1,4‐polybutadiene, (b) 54% trans, 41% cis, 1,4‐polybutadiene, and (c) 86% 1,2‐polybutadiene. G(‐cis CC) and G(‐trans CC), were similar and decreased with dose from ≈ 40 for 0‐1 MGy to 5 for 5‐10 MGy. G(‐double bonds) and G(crosslink) were comparable, indicating that crosslinking occurred through the double bonds. G(crosslink) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Cross-linking produces a more rigid structure with anisotropic chain motions, which gives broadened line widths in NMR spectra. For example, O'Donnell and Whittaker [40] have studied cross-linking in cis-polybutadiene and shown that the line widths increased significantly upon γ-irradiation (or with increasing crosslink density); Yu et al [41] observed a drastically increased line width in HP&HT cross-linked (vinyl) 1,2-polybutadiene using solid-state 13 C CP NMR. However, in this case, the line widths of the F-composite's spectrum did not increase after the 1.7 GPa treatment, which indicates that nylon-6 does not become cross-linked.…”
Section: Polymorphism and Cross-linking Properties By Solid State Nmrmentioning
confidence: 99%
“…Cross-linking produces a more rigid structure with anisotropic chain motions, which gives broadened line widths in NMR spectra. For example, O'Donnell and Whittaker [40] have studied cross-linking in cis-polybutadiene and shown that the line widths increased significantly upon γ-irradiation (or with increasing crosslink density); Yu et al [41] observed a drastically increased line width in HP&HT cross-linked (vinyl) 1,2-polybutadiene using solid-state 13 C CP NMR. However, in this case, the line widths of the F-composite's spectrum did not increase after the 1.7 GPa treatment, which indicates that nylon-6 does not become cross-linked.…”
Section: Polymorphism and Cross-linking Properties By Solid State Nmrmentioning
confidence: 99%
“…The effects of high‐energy radiation on PE,38–41 and other polyolefins,42–44 have been investigated previously by using 13 C NMR spectroscopy. In this work, the formation of saturated end‐groups and the consumption of double bonds on irradiation was confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…They are attributed to the resonances of the cis-aliphatic, cis-olefinic, and trans-aliphatic carbons, respectively. 4,6,21 The very low intensity of the peak at 33.6 ppm indicates that the amount of trans structural units in the BR sample was very small. The spectra of the BR samples which had been compressed at 100 and 120ЊC (i.e., BR-2 and BR-3) were very similar to that of BR-0, indicating that the crosslinking densities of these two samples were small.…”
Section: E20mentioning
confidence: 99%
“…NR and SBR, BR can be crosslinked by crosslinking agents such as sulfur and peroxides 2,4,5 or by high-energy radiation. 2,6 Many research recis-1,4-polybutadiene, commonly called butadiene sults [4][5][6][7][8][9][10] indicate that the crosslinking reaction rubber (BR), is a synthetic rubber whose producmechanisms and the structures and properties of tion ranks only after natural rubber (NR) and the crosslinked rubbers were very different when styrene-butadiene rubber (SBR). 1 Crosslinked different crosslinking agents were used or when BR has excellent abrasion resistance, 1-3 good lowthe crosslinking conditions were different.…”
Section: Introductionmentioning
confidence: 99%